Peningkatan Efisiensi Produksi Pakan dan Keselamatan Kerja di Kelompok Ternak 99 Farm Melalui Implementasi Mesin Pencacah Rumput Hemat Energi - Worldailmi, Elanjati; Annisa, Putri Dwi; Wahyuni, Elvira Sukma; Masalik, Hasan; Fauziyah, Nada Putri; Ningtyas, Anggun Galuh Puspita (Universitas Islam Indonesia, 2025)
The 99 Farm Livestock Group faces challenges in increasing feed production efficiency and occupational safety and health (OHS). These challenges are caused by the use of inefficient and unergonomic grass chopping machines, which pose risks to livestock farmers' safety and increase operational costs. This community service program aims to address these issues by introducing energy-efficient grass chopping machines designed with ergonomic and OHS aspects in mind. This study examines the impact of implementing this technology on livestock farmers' operational efficiency and welfare. The results show a significant increase in the efficiency of the grass chopping process, reduced operational costs, and improved working conditions for livestock farmers. The implementation of this technology is also expected to be an example for other livestock farmers to implement more sustainable and safe practices.